The Postoperatory of Abdominal Surgery: Retrospective Analysis. Risk Factors. Evaluation of Therapy and Prognosis - Cid, Alberto; Jubin, Juan A; Vesperoni, Héctor; Verderosa, Walter; Rodrigo, Carlos; Arismendi, Alberto; Medina, Mario (Cirugía del Uruguay, 1979)
The paper contains an analysis of 100 po'stoperatories of abdominal surgery patients interned in an Intensive Care Unit; these were divided into two groups: those who suffered from peritonitis and those who did not.